STOCK VALUATION OF PT. SAMUDERA INDONESIA TBK. - Ridho Azhari, Muhammad
Indonesia aims to increase its GDP from the marine sector and uphold downstream policies, particularly in the mining sector. Government of Indonesia (GOI) is optimistic about Indonesia's potential as one of the world's largest archipelagic nations. The implementation of these policies will benefit the industrial sector and the shipping industry by increasing the number of shiploads of raw materials transported to smelters. PT. Samudera Indonesia Tbk., one of Indonesia's largest shipping companies, has the potential to capitalize on these opportunities. Despite a significant increase in revenue from 2020 to 2022, the stock price has been declining since mid-2022, despite the positive sentiment in the Indonesian maritime sector and shipping industry. The industry analysis using Porter’s 5 Forces shows the competition among shipping companies in Indonesia is quite high, it requires a good sustainable competitive advantage from the company in order to maintain a big market share in the shipping and logistics industry. This research computes an intrinsic value for PT. Samudera Indonesia Tbk. by using the Discounted Cash Flow method (DCF), and conducts relative valuation by using Enterprise Value (EV) to EBITDA. Based on the DCF method, the company has an intrinsic value of 1,39 USD per share, which is undervalued compared to the current stock price at 0,024 USD per share. Based on the Enterprise Value to EBITDA, PT. Samudera Indonesia has an EV to EBITDA of -0,08 (negative 0,08); while its peers have an average EV to EBITDA of 2,91; this shows that PT. Samudera Indonesia is undervalued compared to its peers. Based on these results, the author recommends to buy the stock of PT. Samudera Indonesia Tbk., because the stock price currently lower than its intrinsic value and has a low EV to EBITDA ratio compared to its peers.